A Surface Protein From Lactobacillus plantarum Increases the Adhesion of Lactobacillus Strains to Human Epithelial Cells - Wang, Guangqiang; Zhang, Minghui; Zhao, Jianxin; Xia, Yongjun; Lai, Phoency F.-H.; Ai, Lianzhong (Frontiers in Microbiology, 2018)
Adhesion to epithelial cells is considered important for Lactobacillus to exert probiotic effects. In this study, we found that trypsin treatment decreased the adhesion ability of Lactobacillus plantarum AR326 and AR269, which exhibit good adhesion ability, and surface proteins extracts increased the adhesion of the strains with poor adhesion ability. By SDS-PAGE and mass spectrometry analysis, the main component of the surface proteins was detected and identified as a protein of approximately 37 kDa. It was 100% homologous with glyceraldehyde-3-phosphate dehydrogenase (GAPDH) from L. plantarum WCFS1. The adhesion of AR326 and AR269 was decreased significantly by blocking with the anti-GAPDH antibody, and GAPDH restored the adhesion of AR326 and AR269 treated with trypsin. In addition, purified GAPDH significantly increased the adhesion of the strains with poor adhesion ability. These results indicated that GAPDH mediates the adhesion of these highly adhesive lactobacilli to epithelial cells and can be used to improve the adhesion ability of probiotics or other bacteria of interest.